(3GdCeGdjs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3GdhQGbjf HGdbGgQI s)
(3ChdgG (B:s
(3eSCdI(B: (3bGd GdTjN eedjkG HGdbGgQI SfI (B613: (3GdVeGFQ GdhGbYI ddQHW s
(3BNQgG (B:s
(3aGYJbO GddHS aj Gdbdjd ddGNJUGQ, hde jYJbO aj GdcKjQ hGddg SHMGfg hJYGdi CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3GdCeGdj Ydi eSGFd eWdbI aj GdfMhs
(3hHgG fXGe GdJYbjHI hocJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdfMhs